2019
DOI: 10.1136/bmjopen-2018-024400
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter emissions of four types of one cigarette brand with and without additives: a laser spectrometric particulate matter analysis of secondhand smoke

Abstract: ObjectiveInhaled particulate matter (PM) in secondhand smoke (SHS) is deleterious for smokers and non-smokers. Different additives in cigarettes might effect the amount of PM. This study aimed to assess the influence of additives on the PM emissions from different cigarette types in SHS.DesignAn experimental study of PM measuring in SHS of cigarettes without exposition of any person.MethodThe concentrations of PM (PM10, PM2.5 and PM1) in SHS of four different types of cigarettes of the brand Lucky Strike, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Two cigarillo brands emitted less PM, and three brands showed similar PM values compared to the reference cigarette. These variations of PM emissions relative to the reference cigarette are consistent with previous ToPIQ studies on cigarettes, where different brands showed likewise more or fewer PM emissions compared to the reference cigarette within a similar range of percentage variation [29,31,34]. Our results differ slightly from studies of particle emissions of six cigars, three cigarillos, and four cigarettes performed in an unventilated 20 m 3 chamber [35].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Two cigarillo brands emitted less PM, and three brands showed similar PM values compared to the reference cigarette. These variations of PM emissions relative to the reference cigarette are consistent with previous ToPIQ studies on cigarettes, where different brands showed likewise more or fewer PM emissions compared to the reference cigarette within a similar range of percentage variation [29,31,34]. Our results differ slightly from studies of particle emissions of six cigars, three cigarillos, and four cigarettes performed in an unventilated 20 m 3 chamber [35].…”
Section: Discussionsupporting
confidence: 91%
“…The reported amounts of the reference cigarette are as follows: tar 9.4 mg, nicotine: 0.73 mg, CO: 12 mg [ 26 ]. For comparison, the reported amounts of the “regular strong” and popular cigarette brands Marlboro Red and Lucky Strike Original Red are as follows: tar 10 mg, nicotine: 0.8 mg, CO: 10 mg [ 28 , 29 ]. For the series of measurements, 20 pieces of each tobacco product were used.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, Rustemeier et al [40] stated in 2002 that additives in cigarettes increase PM levels in a range from 13% to 28%. Braun et al [17] found higher PM burden by cigarettes with additives in comparison to those of the same brand without additives too. An analysis of the formerly secret documents of the tobacco industry released in 2011 by Wertz et al [41], ascertained post hoc protocol alterations in four peer-reviewed publications conducted by Philip Morris.…”
Section: Discussionmentioning
confidence: 96%
“…This study, much like to previous ToPIQ studies, focused on the comparison of the investigated tobacco products with a reference cigarette [14][15][16][17]24,31,43,59]. Especially for comparison with guideline values or other investigations, the absolute data are stated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation